2013
DOI: 10.1089/scd.2012.0273
|View full text |Cite
|
Sign up to set email alerts
|

Factors Secreted by Mesenchymal Stem Cells and Endothelial Progenitor Cells Have Complementary Effects on Angiogenesis In Vitro

Abstract: Stem cell-based therapy for myocardial regeneration has reported several functional improvements that are attributed mostly to the paracrine effects stimulating angiogenesis and cell survival. This study was conducted to comparatively evaluate the potential of factors secreted by mesenchymal stem cells (MSCs) in normoxic and hypoxic conditions to promote tissue repair by sustaining endothelial cell (EC) adhesion and proliferation and conferring protection against apoptosis. To this aim, a conditioned medium (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
121
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 27 publications
2
121
0
Order By: Relevance
“…These include but are not limited to vascular endothelial growth factor, stromal cell-derived factor 1a (SDF-1a), basic fibroblast growth factor, brain-derived neurotrophic factor. 25,30,31 Our data indicate that EPCs can be exploited to provide survival cues to axons after ischemic but not mechanical injury. One reason for this difference in response may be related to the severity of injury incurred through mechanical trauma in relation to ischemic injury.…”
Section: Discussionmentioning
confidence: 77%
“…These include but are not limited to vascular endothelial growth factor, stromal cell-derived factor 1a (SDF-1a), basic fibroblast growth factor, brain-derived neurotrophic factor. 25,30,31 Our data indicate that EPCs can be exploited to provide survival cues to axons after ischemic but not mechanical injury. One reason for this difference in response may be related to the severity of injury incurred through mechanical trauma in relation to ischemic injury.…”
Section: Discussionmentioning
confidence: 77%
“…[9][10][11] There is only 3%-14% oxygen in brain. 12 Hypoxia 13 can affect the secretion of paracrine factors, 14 alter gene expression of MSCs 15,16 and enhance proliferation of MSCs. [17][18][19][20][21] The amount of serum present in the culture media also affects stem cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…14,15,32 Hypoxia caused an increase in the secretion of transforming growth factor-β2; insulin-like growth factor (IGF) binding proteins 2, 3, 4 and 6; IGF-II and interleukin-7, 33,34 and reduced the secretion of stromal cell derived factor-1, macrophage colony stimulating factor, interleukin-1 receptor antagonist, RANTES, chemokine (C-X-C motif) ligand 1, lactate dehydrogenase and chemokine (C-X-C motif) ligand 10 by MSCs. 16,35 In short, hypoxia changes the paracrine secretions of MSCs, which would have implications for the role they play in reducing the loss of function in the brain after cerebral ischemia. Exposure to a hypoxic environment leads to obvious changes in cellular physiology.…”
mentioning
confidence: 99%
“…32 MSCs in in vitro condition express a small amount of MHC I and are negative for MHC II, CD40, and CD86 and, therefore, is unable to stimulate immune reaction in the host. 33 It has been documented that MSCs play their immunomodulatory functions via cell contact or secretion of certain factors. 34 Previous investigations demonstrated that DCs are the most cells which are under immunomodulatory functions of MSCs.…”
Section: Discussionmentioning
confidence: 99%